The Relationship Between Galen’s Personality Type Theory and Emotional Intelligence Level - Olyvia Sita Aldisa Thadea; Suhartono Taat Putra; I Gusti Ngurah Gunadi Sindhu Putra (Biomolecular and Health Science Journal, 2018)
Introduction: Personality is a behavior and mindset pattern that is typical for each person in responding to every event or stimulus in his environment. Galen's theory has classified personality types into four types they are Sanguinis, Choleric, Melancholy, and Plegmatis. The level of emotional intelligence shows a person's ability to deal with demands and pressures to achieve their best in thinking and behaving appropriately. This study aims to prove the relationship between personality types based on Galen's theory with emotional intelligence level in preclinical medical students.Methods: This study is a comparative study using an online questionnaire instrument on emotional intelligence and personality type tests compiled by Florence Littauer. This research variables are the emotional intelligence level and personality type. This study used data from 100 respondents, then data was analyzed using Chi Square test.Results: From 100 respondents, dominant personality type is Sanguinis 35%, followed by Choleric 13%, Melancholy 27%, and Plegmatis 25%. There were no respondent who showed a low level of emotional intelligence in this study. 64% of respondents have a high level of emotional intelligence, while the remaining 36% have a moderate level. Chi Square test shows p value is 0.032.Conclusion: There is a relationship between personality types based on Galen's theory with emotional intelligence level on medical students in Faculty of Medicine, Universitas Airlangga.